Simulating putative Enceladus-like conditions: The possibility of biological methane production on Saturn's icy moon. Issue Volume 14:Issue S345(2019) (August 2018) - Taubner, Ruth-Sophie; Pappenreiter, Patricia; Zwicker, Jennifer; Smrzka, Daniel; Pruckner, Christian; Kolar, Philipp; Bernacchi, Sébastien; Seifert, Arne H.; Krajete, Alexander; Bach, Wolfgang; Peckmann, Jörn; Paulik, Christian; et al.
Abstract: In this study (Taubner et al. 2018 ), three different methanogenic archaea ( Methanothermococcus okinawensis, Methanothermobacter marburgensis, and Methanococcus villosus ) were tested for metabolic activities and growth under putative Enceladus-like conditions, including high pressure experiments and tests on the tolerance towards potential gaseous and liquid inhibitors detected in Enceladus' plume. In particular, M. okinawensis, an isolate from a deep marine trench (Takai et al. 2002 ), showed tolerance towards all of the added inhibitors and maintained methanogenesis even in the range of 10 to 50 bar. Further, we were able to show that H2 production based on serpentinization may be sufficient to fuel such methanogenic life on Enceladus. The experiments revealed that methanogenesis could, in principle, be feasible under Enceladus-like conditions.